Wearproofness of discrete surfaces in the conditions of fretting-wearness - Марчук, В.Є. (Proceedings of National Aviation University, 2010)
Experimental researches of fretting-wearproofness of discrete surfaces are presented on the steel 30ХГСA. Determined that discrete surfaces exceed a wearproofness 1,8-2,44 times on the smooth (not discrete) surface. Kinetics of process of fretting-wearprofness of discrete surfaces is studied and the physical model of their wear, which consists of three periods of developmen is formed.